Treatment with Fenofibrate plus a low dose of Benznidazole attenuates cardiac dysfunction in experimental Chagas disease - Cevey, Ágata Carolina (2017)
Trypanosoma cruzi induces serious cardiac alterations during the chronic infection. Intense inflammatory response observed from the beginning of infection, is critical for the control of parasite proliferation and evolution of Chagas disease. Peroxisome proliferator-activated receptors (PPAR)-α, are known to modulate inflammation. In this study we investigated whether a PPAR-α agonist, Fenofibrate, improves cardiac function and inflammatory parameters in a murine model of T. cruzi infection. BALB/c mice were sequentially infected with two T. cruzi strains of different genetic background. Benznidazole, commonly used as trypanocidal drug, cleared parasites but did not preclude cardiac pathology, resembling what is found in human chronic chagasic cardiomyopathy. Fenofibrate treatment restored to normal values the ejection and shortening fractions, left ventricular end-diastolic, left ventricular end-systolic diameter, and isovolumic relaxation time. Moreover, it reduced cardiac inflammation and fibrosis, decreased the expression of pro-inflammatory (IL-6, TNF-α and NOS2) and heart remodeling mediators (MMP-9 and CTGF), and reduced serum creatine kinase activity. The fact that Fenofibrate partially inhibited NOS2 expression and NO release in the presence of a PPAR-α non-competitive inhibitor, suggested it also acted through PPAR-α-independent pathways. Since IκBα cytosolic degradation was inhibited by Fenofibrate, it can be concluded that the NFκB pathway has a role in its effects. Thus, we demonstrate that Fenofibrate acts through PPAR-α-dependent and -independent pathways. Our study shows that combined treatment with Fenofibrate plus Benznidazole is able both to reverse the cardiac dysfunction associated with the ongoing inflammatory response and fibrosis and to attain parasite clearance in an experimental model of Chagas disease.